2014
DOI: 10.7903/ijcse.1074
|View full text |Cite
|
Sign up to set email alerts
|

How Do Different Internet Use Functions Affect Bridging and Bonding Social Capital? An Empirical Study of the Chinese International Students in Japan

Abstract: This study examines the relationship between Internet use and social capital in an intercultural context and investigates how different Internet use functions are related to social capital. Data were collected from the survey among 155 Chinese international students studying in Japan's universities. The results showed that Internet use intensity negatively influenced individuals' bonding social capital. It was also found that the use of the Internet for staying informed would have positive effects on bridging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
0
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 33 publications
1
0
0
4
Order By: Relevance
“…Previous findings showed that IM helps to maintain relationships with strong ties and, therefore, serves the need of belongingness (Cui, 2016;Ledbetter et al, 2016;Quan-Haase & Young, 2010;Timmis, 2012). Hence, using IM communication likely plays a less contradictory role for well-being outcomes concerning relationship satisfaction than has been found for the use of social media in general (e.g., Guo et al, 2014;McCrae et al, 2017;Valkenburg & Peter, 2007a). We found that other (control) variables were also associated with relationship satisfaction as was expected based on previous research.…”
Section: Discussionsupporting
confidence: 81%
“…Previous findings showed that IM helps to maintain relationships with strong ties and, therefore, serves the need of belongingness (Cui, 2016;Ledbetter et al, 2016;Quan-Haase & Young, 2010;Timmis, 2012). Hence, using IM communication likely plays a less contradictory role for well-being outcomes concerning relationship satisfaction than has been found for the use of social media in general (e.g., Guo et al, 2014;McCrae et al, 2017;Valkenburg & Peter, 2007a). We found that other (control) variables were also associated with relationship satisfaction as was expected based on previous research.…”
Section: Discussionsupporting
confidence: 81%
“…Konsep modal sosial menurut Bourdieu (1986) adalah jumlah dari sumber-sumber (resources) baik nyata maupun virtual, yang diterima baik oleh individu maupun kelompok sebagai akibat dari ketahanan jaringan hubungan pribadi dan kelompok. Coleman menggambarkan modal sosial sebagai sebuah akumulasi hubungan antarpersonal dan dapat mendorong kegiatankegiatan yang konstruktif antarpersonal dalam jaringan sehingga secara konseptual diparalelkan pada modal manusia, modal fisik, dan modal keuangan (Coleman dalam Guo, Li & Ito, 2014). Sedangkan, Putnam berpendapat bahwa jaringan sosial, norma yang bersifat timbal balik, serta kepercayaan merupakan komponen utama pembentuk modal sosial (Putnam, 2000).…”
Section: Pendahuluanunclassified
“…Sedangkan, Putnam berpendapat bahwa jaringan sosial, norma yang bersifat timbal balik, serta kepercayaan merupakan komponen utama pembentuk modal sosial (Putnam, 2000). Dari dua sudut pandang besar ini juga memunculkan dua pandangan berbeda yaitu: pandangan modal sosial sebagai 'private goods' (Bourdieu, 1986) dan modal sosial sebagai 'collective' (Coleman dalam Guo, Li & Ito, 2014).…”
Section: Pendahuluanunclassified
See 2 more Smart Citations